A Chatbot Generator for Improved Digital Governance - Christos Bouras; Damianos Diasakos; Chrysostomos Katsigiannis; Vasileios Kokkinos; Apostolos Gkamas; Nikos Karacapilidis; Yannis Charalabidis; Zoi Lachana; Charalampos Alexopoulos; Theodoros Papadopoulos; Georgios Karamanolis; Michail Psalidas (20th European Mediterranean & Middle Eastern Conference on Information Systems (EMCIS 2023), December 11 – 12, 2023, Dubai, UAE, 2023)
Chatbots, the pioneering conversational artificial intelligence (AI) agents, have experienced remarkable growth and integration in various domains. In modern societies, chatbots have emerged as transformative digital entities, revolutionizing the way humans interact with technology. These conversational AI agents have transcended their initial applications to become integral parts of various industries and daily life. One of the most prominent roles of chatbots is in customer service, where they offer round-the-clock assistance, swift issue resolution, and personalized interactions.By handling routine queries and tasks, chatbots free up human agents to focus on complex and specialized issues, thus optimizing overall efficiency and customer satisfaction. To this end, this paper aims to present and describe the architecture of a novel chatbot generator with improved functionality in terms of quality of communication with end users and level of provided services, with a specialized infrastructure understanding the Greek language. The chatbot generator was developed in the framework of a research project and will be pilot tested by two end-users, the National Bank of Greece (NBG) and the General Secretariat for Information Systems & Digital Governance (GSIS-DG).